Rancang Bangun Sistem Penjualan pada Toko Sakinah Menggunakan Metode Design Sprint - Ruhaya Hayuni; Fajar Ratnawati (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
With technological advancements, digitalization in business has become a crucial factor in enhancing sales effectiveness, especially for micro, small, and medium enterprises (MSMEs). Toko Sakinah, which has been operating for nearly 35 years in Bengkalis, still relies on conventional sales methods, such as WhatsApp transactions or direct store visits. This approach limits market reach and operational efficiency. Therefore, this study aims to design and develop a web-based digital sales system using the Design Sprint method to improve sales effectiveness at Toko Sakinah.The Design Sprint method is applied to develop the system quickly and systematically, focusing on understanding user needs, prototyping, and testing solutions before full implementation. The result of this research is a sales website that facilitates online product ordering, sales reporting, and interaction between buyers and store owners. This website is expected to expand market reach, enhance sales efficiency, and serve as a development model that can be replicated by other MSMEs.